2020
DOI: 10.1177/2151459320939546
|View full text |Cite
|
Sign up to set email alerts
|

High- Versus Low-Energy Acetabular Fracture Outcomes in the Geriatric Population

Abstract: Introduction: High-energy mechanisms of acetabular fracture in the geriatric population are becoming increasingly common as older adults remain active later in life. This study compared outcomes for high- versus low-energy acetabular fractures in older adults. Materials and Methods: We studied outcomes of 22 older adults with acetabular fracture who were treated at a level-I trauma center over a 4-year period. Fourteen patients were categorized as low-energy mechanism of injury, and 8 were identified as a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…A higher V Impact is associated with a bigger impact force exerted in a shorter time (a higher strain rate), which makes the bone prone to fracture during falls [78]. In a recent study, Cecil et al [79] concluded that by increasing the impact energy (velocity), the type of acetabular fracture changes. Also, they stated that the anterior wall fracture is common among elderly people who experience low-energy event trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A higher V Impact is associated with a bigger impact force exerted in a shorter time (a higher strain rate), which makes the bone prone to fracture during falls [78]. In a recent study, Cecil et al [79] concluded that by increasing the impact energy (velocity), the type of acetabular fracture changes. Also, they stated that the anterior wall fracture is common among elderly people who experience low-energy event trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because of the increasing prevalence of high-energy trauma cases in our society, surgical interventions for the treatment of acetabular fractures are becoming increasingly common in trauma centers. 1,3 Currently, open reduction and internal fixation (ORIF) is considered the mainstay treatment of displaced acetabular fractures; however, a subset of patients with these traumatic injuries are not amenable to ORIF because they may be predisposed to early posttraumatic arthritis. 1,4,5 Recently, studies have shown that the use of primary total hip arthroplasty (THA) for these injuries provides sufficient stability and is considered as a suitable substitute for these injury patterns.…”
mentioning
confidence: 99%